Anatomical evidence of an indirect pathway for word repetition. (11th February 2020) - Forkel, Stephanie J.; Rogalski, Emily; Drossinos Sancho, Niki; D'Anna, Lucio; Luque Laguna, Pedro; Sridhar, Jaiashre; Dell'Acqua, Flavio; Weintraub, Sandra; Thompson, Cynthia; Mesulam, M.-Marsel; Catani, Marco
Abstract : Objective: To combine MRI-based cortical morphometry and diffusion white matter tractography to describe the anatomical correlates of repetition deficits in patients with primary progressive aphasia (PPA). Methods: The traditional anatomical model of language identifies a network for word repetition that includes Wernicke and Broca regions directly connected via the arcuate fasciculus. Recent tractography findings of an indirect pathway between Wernicke and Broca regions suggest a critical role of the inferior parietal lobe for repetition. To test whether repetition deficits are associated with damage to the direct or indirect pathway between both regions, tractography analysis was performed in 30 patients with PPA (64.27 ± 8.51 years) and 22 healthy controls. Cortical volume measurements were also extracted from 8 perisylvian language areas connected by the direct and indirect pathways. Results: Compared to healthy controls, patients with PPA presented with reduced performance in repetition tasks and increased damage to most of the perisylvian cortical regions and their connections through the indirect pathway. Repetition deficits were prominent in patients with cortical atrophy of the temporo-parietal region with volumetric reductions of the indirect pathway. Conclusions: The results suggest that in PPA, deficits in repetition are due to damage to the temporo-parietal cortex and its connections to Wernicke and Broca regions. We therefore propose a revised language model that also includes an indirect pathway for repetition, which has important clinical implications for the functional mapping and treatment of neurologic patients.